Challenges in Engaging Students during an Online Health Professions Education Course: An Exploratory, Qualitiative Study - Sana Khan, Brekhna Jamil (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Multiple challenges have raised in medical education after the pandemic due to transition from face-to-face to online learning. One of the major issues faced is related to student engagement. This study aimed to understand the challenges of student engagement in online learning for a health professions education program. Study design: Qualitative explorative study. Place & duration: The study was conducted in the medical education department, institute of health professions education and research, Khyber medical university, Peshawar, Pakistan. For the purpose of data collection, three institutes were involved: Khyber Medical University (KMU), Riphah International University (RIU) and University College of Medicine & Dentistry (UCMD). All three institutes were conducting Masters program in Health Professions Education (MHPE). The study was conducted from 28/02/2021 to 31/08/2021. Methodology: A total of 12 students and six faculty members were recruited from three different Masters in Health Professions Education (MHPE) programs in Pakistan. Semi-structured interviews were recorded on Zoom, two variables assessed on interviews were, defining online student engagement and challenges of student engagement in online learning. The interviews were transcribed onto MS Word files. The files were imported into NVivo v12.0 and analyzed to determine any emergent themes and sub themes. Results: A total of four main themes and eleven sub themes emerged. The themes were: lack of motivation, distractors, lack of faculty development and non-conductive environment. Conclusion: The participants identified lack of student motivation and interest in online learning; technical challenge such as internet connectivity; lack of faculty training; household distractions and a non-conducive environment such as a large class size as the main challenges for online student engagement in a MHPE program.